Weaving the West Psychosocial Care Network of the municipality of São Paulo - Maria do Perpétuo Socorro de Sousa Nóbrega; Alessandra Matheus Domingos; Ana Stella de Azevedo Silveira; Jussara Carvalho dos Santos
ABSTRACT Objective: to understand how health service professionals involved in the care of users in psychic distress perceive the organization of the Psychosocial Care Network (RAPS - Rede de Atenção Psicossocial) in the western region of the city of São Paulo. Method: qualitative approach study conducted with 123 professionals with higher education who work in the care points of the network. A semi-structured interview was performed and data were submitted to the Alceste program for lexical analysis. Results: the network is in process of alignment with the mental health policy and the psychosocial rehabilitation strategy. However, the weaknesses in the work process of teams are related to deficits in human resources, structure, and communication, and to the limited appropriation of their guidelines. Final considerations: there are intense efforts of workers to weave the network, and barriers need to be overcome to support successful actions in mental health care in the territory.